The impact of the COVID‐19 pandemic on eating disorders: A systematic review. Issue 1 (5th April 2022) - J. Devoe, Daniel; Han, Angela; Anderson, Alida; Katzman, Debra K.; Patten, Scott B.; Soumbasis, Andrea; Flanagan, Jordyn; Paslakis, Georgios; Vyver, Ellie; Marcoux, Gisele; Dimitropoulos, Gina
Abstract: Objective: A growing body of evidence suggests that individuals with eating disorders (EDs) have experienced deteriorating symptoms, increased isolation, and an increase in hospital admissions as a result of the COVID‐19 pandemic. Despite this, no systematic reviews have been conducted examining the COVID‐19 and ED peer‐reviewed literature. Therefore, this systematic review aimed to synthesize the impact of the COVID‐19 pandemic on individuals with EDs. Method: Database searches of the peer‐reviewed literature were completed in the subsequent databases: CINAHL, Embase, MEDLINE, and PsycINFO (from November 2019 to October 20, 2021). All research reporting on the relationship between the COVID‐19 pandemic on individuals with EDs were included. Results: Fifty‐three studies met the inclusion criteria, including 36, 485 individuals with EDs. The pooled hospital admissions across the studies demonstrated on average a 48% (pre = 591, post = 876, n  = 10 studies) increase in admissions during the pandemic compared to previous pre‐pandemic timepoints. In this review, 36% of studies ( n  = 19) documented increases in eating disorder symptoms during the pandemic, this increase in eating disorder symptoms were documented in AN, BED, BN, and OFSED patients. Studies also demonstrated increases in anxiety ( n  = 9) and depression ( n  = 8), however patterns of change appeared to be diagnostic and timing specific (e.g., lockdowns). Discussion: We found a large increase in the number of hospitalizations and an increase in ED symptoms, anxiety, depression, and changes to BMI in ED patients during the pandemic. However, these changes appeared to be diagnostic and timing specific. Many qualitative studies described deterioration in ED symptomatology due to decreased access to care and treatment, changes to routine and loss of structure, negative influence of the media, and social isolation. Future studies are needed to focus on pediatric populations, new ED diagnoses, and severity of illness at presentation. Public Significance: The scientific literature suggests that individuals with eating disorders have experienced deteriorating symptoms, increased isolation, and an increase in hospital admissions as a result of the COVID‐19 pandemic. This study synthesized 53 articles and explored the impact of the COVID‐19 pandemic on patients with eating disorders. We found increases in eating disorder symptoms during the pandemic; this increase in eating disorder symptoms was documented in patients with common eating disorders including anorexia nervosa, binge‐eating disorder, bulimia nervosa, and other specified feeding and eating disorders. This review also demonstrated changes in body mass index (an index used to classify underweight, overweight, and obesity in adults) and increases in anxiety and depression during the pandemic compared to previous timepoints; patterns of change appeared to be related to timing of lockdowns. This review provides important information on the impact of COVID‐19 on the physical and mental health of individuals with eating disorders. Resumen: Objetivo: Un creciente conjunto de evidencia sugiere que las personas con trastornos de la conducta alimentaria (TCA) han experimentado síntomas de deterioro, mayor aislamiento y un aumento en los ingresos hospitalarios como resultado de la pandemia de COVID‐19. A pesar de esto, no se han realizado revisiones sistemáticas que examinen la literatura revisada por pares de COVID‐19 y TCA. Por lo tanto, esta revisión sistemática tuvo como objetivo sintetizar el impacto de la pandemia de COVID‐19 en las personas con TCA. Método: Las búsquedas en las bases de datos de la literatura revisada por pares se completaron en las bases de datos posteriores: CINAHL, Embase, MEDLINE y PsycINFO (de noviembre de 2019 al 20 de octubre de 2021). Se incluyeron todos los informes de investigación sobre la relación entre la pandemia de COVID‐19 en individuos con TCA. Resultados: Cincuenta y tres estudios cumplieron los criterios de inclusión, incluyendo 36, 485 individuos con TCA. Los ingresos hospitalarios agrupados en los estudios demostraron en promedio un aumento del 48% (antes = 591, después = 876, n = 10 estudios) en los ingresos durante la pandemia en comparación con los puntos de tiempo previos a la pandemia. En esta revisión, el 36% de los estudios (n = 19) documentaron aumentos en los síntomas del trastorno alimentario durante la pandemia, este aumento en los síntomas del trastorno de la conducta alimentaria se documentó en pacientes con AN, TpA, BN y OSFED. Los estudios también demostraron aumentos en la ansiedad (n = 9) y la depresión (n = 8), sin embargo, los patrones de cambio parecían ser diagnósticos y específicos del momento (por ejemplo, encierros). Discusión: Encontramos un gran aumento en el número de hospitalizaciones y un aumento en los síntomas de TCA, ansiedad, depresión y los cambios en el IMC en pacientes con TCA durante la pandemia. Sin embargo, estos cambios parecían ser diagnósticos y específicos del momento. Muchos estudios cualitativos describieron un deterioro en la sintomatología del trastorno de la conducta alimentaria (TCA) debido a la disminución del acceso a la atención y el tratamiento, los cambios en la rutina y la pérdida de estructura, la influencia negativa de los medios de comunicación y el aislamiento social. Se necesitan estudios futuros para centrarse en las poblaciones pediátricas, los nuevos diagnósticos de TCA y la gravedad de la enfermedad al momento de la presentación. Palabras clave: trastornos de la conducta alimentaria, pandemia, COVID‐19